The effect of Eurycoma Longifolia on the regulation of reproductive hormones in young males. (9th February 2021) - Chan, Kai Quin; Stewart, Claire; Chester, Neil; Hamzah, Sareena H.; Yusof, Ashril
Abstract: Eurycoma longifolia supplementation increases testosterone levels in humans via activation of the hypothalamic‐pituitary‐gonadal axis and/or the hypothalamic‐pituitary‐adrenal axis mainly in older adults and nonhealthy populations. This study aimed to assess the impact of Eurycoma longifolia on the hypothalamic‐pituitary‐gonadal and hypothalamic‐pituitary‐adrenal axes in healthy young males since this might promote functional testosterone prowess. Thirty‐two males (24.4 ± 4.7 years; 1.74 ± 0.07 m; 73.7 ± 8.4 kg) in a placebo‐controlled, double‐blind, matched‐paired study received 600 mg/day Eurycoma longifolia or placebo for two weeks. Blood analysis using repeated measures analysis of variance showed significant interaction and time effects for testosterone (F1, 30  = 9.04, p  = .005), free testosterone (F1, 30  = 7.13, p  = .012) and estradiol (F1, 30  = 8.07, p  = .008) levels in favour of the treatment group, while luteinising hormone, follicle‐stimulating hormone and sexual hormone‐binding globulin did not. The lack of changes in luteinising hormone and follicle‐stimulating hormone levels suggests that a lesser role played by Eurycoma longifolia in activating the hypothalamic‐pituitary‐gonadal axis in the young adults. The raised testosterone level may be due to a greater rate of hormone production via the hypothalamic‐pituitary‐adrenal axis. The supplementation of Eurycoma longifolia for two weeks demonstrates steroidogenic effects on young men were dose‐related. Consequently, the raised testosterone following Eurycoma longifolia supplementations could benefit muscle and strength gain in young adults.